APLIKASI SISTEM MONITORING PENJUALAN DISTRIBUTOR DI PR. SUMBER DJAYA - Setyowibowo, Sigit; Nugroho, Timtim Sulistiono (DINAMIKA DOTCOM, 2012)
Marketing Unit is a unit in one of the PR. Djaya sources that have a role in the process of marketing to contribute to the companys sales. Based on examination of Sales Monitoring Applications that are running there are things that can be developed further, which simplify and accelerate the computation recapitulation bills and distributor sales effectiveness. With the optimized system is expected to meet sales targets planned. Hopefully this simple information systems can be an additional solution to overcome the problems in the implementation and reporting system that is running. Key Words: Application Monitoring Sales Distributor in PR. sources Djaya